Dialectic between the Law and the Gospel in the Context of Indonesia - Emanuel Gerrit Singgih (STT Mamasa, 2021)
In the theological context of Indonesian churches there is an unhealthy polarization between the Gospel and the Law. It arose out of a misunderstanding the Old Testament as Law and the New Testament as Gospel. Here it is attempted to overcome this polarization by utilizing the thinking of Paul and Calvin, where the Law and the Gospel are regarded as having a dialectical relationship.